Sampelong Batu Putiah: Komposisi Musik untuk Orkestra - Aluna Aluna; Hadaci Sidik; Delfi Enida (MUSICA : Journal of Music, 2021)
Sampleong as one of the traditional Minangkabau music that grows and develops in the Tolang Mau area, kec. Please, kab. 50 Kota has a unique and interesting musical idiom to be developed as a musical idea in the creation of new musical compositions. Sampleong is a traditional Minangkabau music performance that is performed in a duet between a singer and a sample of wind music player. At the beginning of its growth, it had a mystical feel, but along with the development of religion and culture, it turned into a function of entertainment music. This mystical atmosphere is reflected in the melodic aesthetics of the songs contained in the sampleong music. Sampleong music has several songs, one of which is Batu Putiah. In this paper, the melody of the sampleong Batu Putiah is taken as the basis for the creation of a thematic new musical composition that is worked on in an orchestral format. This material was worked out through examination of, exploration, and experimentation of musical elements, so that it became a new musical that represents the journey of Sampelong without losing the distinctiveness of Sampleong itself.Keywords: Sampelong, Batu Putiah, CompositionABSTRAKSampelong sebagai salah satu musik tradisional minangkabau yang tumbuh dan berkembang di daerah Tolang Mau, kec. Mungka, kab. 50 Kota memiliki idiom musikal yang unik dan menarik untuk dikembangkan sebagai ide musikal dalam penciptaan komposisi musik baru. Sampelong merupakan pertunjukan musik tradisional minangkabau yang ditampilkan secara duet antara penyanyi dan pemain musik tiup sampelong. Pada awal pertumbuhannya sampelong memiliki nuansa mistik, namun seiring dengan perkembangan agama dan kebudayaan, sampelong berubah fungsi menjadi musik hiburan. Suasana mistik ini tergambar dalam estetika melodi yang dimiliki oleh lagu-lagu yang terdapat pada musik sampelong. Musik sampelong memiliki beberapa lagu, salah satunya adalah Batu Putiah. Pada tulisan ini, melodi lagu sampelong Batu Putiah diambil sebagai dasar terciptanya sebuah tematik komposisi musik baru yang digarap ke dalam format orkestra. Komposisi ini digarap melalui identifikasi, eksplorasi, dan eksperimentasi terhadap unsur-unsur musikal, sehingga menjadi musikal baru yang mewakili perjalanan Sampelong tanpa menghilangkan ciri khas dari Sampelong itu sendiri.Kata Kunci: Sampelong, Batu Putiah, Komposisi